HUBUNGAN ANTARA KETERAMPILAN KOMUNIKASI SISWA DAN PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR IPA SISWA KELAS VIII SMP NEGERI 10 KECAMATAN UMBULHARJO YOGYAKARTA TAHUN AJARAN 2014/2015 - Syahrial Nurasa; Nyoman Erosa; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
This study aims to determine (1) the tendency of students communication skills, attention to parents and learning achievements of natural science students of SMP Negeri 10 Umbulharjo District of Yogyakarta; and (2) there is a positive and significant relationship between students communication skills and attention of parents with learning achievement either independently or together. This research ex post facto quantitative certain model implemented in SMP Negeri 10 District of Umbulharjo Yogyakarta, this study bersampel 167 students. The results showed that (1) the tendency of each - each independent variable in the high category and science learning achievement in the category of very high; (2) the relationship between each - each variable with learning achievement seen from the students' communication skills sig 0.009 <0.05 and attention of parents sig 0.00 <0.05; and (3) the relationship between the two variables with student achievement seen from the value of F count = 7.849> F table = 3.05 with a significance of 5%. So that the students' communication skills and attention of parents have a relationship to improve learning achievement IPA class VIII SMP Negeri 10 districts of Umbulharjo Yogyakarta. The relative contribution on students' communication skills amount 20.34% and the attention of parents amount 79.66%. While effective contribution on communication skills of students amount 2.3% and the attention of parents amount 6.4%. Thus to improve learning achievement IPA it is necessary pay attention to students' communication skills and attention from the parents of students.